Evaluation of the efficacy of biocides in removing biofilms produced by multidrug-resistant Pseudomonas aeruginosa (Research, Society and Development, 2020)
Pseudomonas aeruginosa is one of the most frequent pathogens in infections affecting burn patients, having as an important determinant of pathogenicity its ability to form biofilms. The present work aims to evaluate the effectiveness of biocidal solutions: 4% chlorhexidine, 1% sodium hypochlorite, 5% hydrogen peroxide and 70% alcohol on removal P. aeruginosa multidrug-resistant biofilms. This is a descriptive study with a quantitative approach. Biofilms from nine strains of P. aeruginosa, of different clonal types, were evaluated. Eight strains were carbapenem-resistant and one susceptible, collected from burned patients and balneotherapy tables. Strains were grown together with stainless steel coupons and incubated for 24 h. Subsequently, the coupons were treated with and without biocides, at contact times of 15, 5 and 0 minutes. Biofilm removal was assessed by counting viable cells obtained from coupons with and without treatment. The minimum inhibitory concentration for imipenem and meropenem was determined by using the epsilometric method. Biofilm formation was observed in all coupons not treated with biocides. However, there was no count of viable cells after contact of the biofilm with all biocidal solutions, in all times. The minimum inhibitory concentration to carbapenems varied between 16 to ≥ 32µg / mL. It was concluded that all the disinfectant solutions evaluated were effective in removing biofilms produced by the studied P. aeruginosa strains.